Online Promotion Strategy of Coffee Shop Carakita through Social Media Instagram to increase Sales in 2024 - Vernada Alvia Saputri; Sitta Sari, Sovia (Jogjakarta Communication Conference (JCC), 2025)
This study aims to analyze the online promotion strategy carried out by CaraKita coffee shop through Instagram social media in an effort to increase sales in 2024. The background of this research comes from the rapid growth of the coffee shop industry in Indonesia, especially in Yogyakarta, which encourages business actors to utilize digital platforms as a promotional medium. By using the theory of online promotion strategy and promotion mix theory. The method used in this research is qualitative, with a descriptive analysis approach. The data in this study were collected through interviews and documentation. The findings of this study show that the main objectives of CaraKita coffee shop in implementing online promotion strategies are to reach new target markets and increase sales. This goal is achieved by utilizing three elements of the promotional mix namely advertising, sales promotion, and public relations. Of the three, the most relied upon is sales promotion because it is most effective in attracting attention and encouraging purchases.